Assessment of endothelial dysfunction by brachial artery flow-mediated dilatation in postmenopausal women at low risk for cardiovascular disease - Piyushi Sharad; Neha Agarwal; Seema Chopra; Vanita Jain; Pooja Sikka; Ajay Bahl; Nayana Gaba (Wolters Kluwer Medknow Publications, 2021)
Objective: The objective is to compare endothelial dysfunction measured by brachial artery flow-mediated dilation (BAFMD) in nonobese, nondiabetic post-menopausal women with their age-matched menstruating controls and to identify the correlation of BAFMD with Framingham risk score (FRS) and with the individual parameters of FRS in low-risk women. Methods: This study was done in the department of Obstetrics and Gynaecology, Chandigarh, India, for 1 year. Fifty postmenopausal and 50 menstruating females aged 45-55 years who were nondiabetic and nonobese and were low risk according to FRS were selected as cases and controls, respectively. All cases and controls were age-matched. The diameter of the brachial artery and the blood flow in it was measured at rest. Ischemia was produced and released after 5 min. The maximum blood flow velocity diameter of the brachial artery was measured. After 10 min of reactive hyperemia, 400 μg of sublingual nitrate was given, and vasodilatation mediated by nitroglycerine was subsequently measured. Results: Menopause did not have any significant effect on the endothelial dysfunction as measured by the brachial artery flow-mediated dilatation (P = 0.74) but did influence vascular smooth muscle as measured by nitroglycerine-mediated dilatation (P = 0.028). A significant correlation was found between flow-mediated dilatation with FRS helps us conclude that flow-mediated dilation is a reliable tool to estimate the cardiovascular risk (P < 0.001). A strong correlation was found between nitroglycerine-mediated dilatation and flow-mediated dilatation, demonstrating that both endothelial dysfunction and vascular smooth muscle are interrelated (P < 0.001). Conclusion: Menopause did not affect endothelial function, but it has a significant effect on vascular smooth muscle function. To know the effect of longer duration of menopause on vascular function in elderly women further studies with large number of postmenopausal women of different duration of menopause, may be needed.